THE RELATIONSHIP BETWEEN ENERGY INTAKE, MACRONUTRIENS, AND MATERNAL NUTRITIONAL KNOWLEDGE WITH THE NUTRITIONAL STATUS OF TODDLES AGED 2-5 YEARS AT MENUR PUBLIC HEALTH CENTRE IN SURABAYA - Firginia, Nabila (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The state of one's nutritional status is the outcome of striking a balance between the amount of nutrients obtained from meals and the amount required for bodily metabolism. Obesity is likely to persist into adulthood if it starts in toddlerhood. The incidence of obesity can be caused by various factors. The purpose of this study is to ascertain how energy intake, macronutrients, and maternal nutritional knowledge relate to nutritional status of toddlers at Menur Surabaya Health Center between the ages of two and five. A case-control design was employed in this investigation. The toddlers in the case group of this study were overweight and obese, while the control group consisted of toddlers who were not overweight and obese. There were fifty responders in each group, for a total sample size of 100 for this study. Data were gathered using a multiple-choice food memory test sheet for mothers and a food recall test administered three times in a 24-hour period. Nutritional status of children utilizing indexes of weight and height measurement. Chi-square test and odds ratio were employed in both bivariate data analysis. The findings indicated that while there was no correlation between maternal nutritional knowledge (p=0.205; OR=1,7) and the nutritional status of toddlers, there was a relationship between energy intake (p=0.000; OR=38,5), protein (p=0.000; OR=27,9), fat (p=0.000; OR=41,0), and carbohydrates (p=0.000; OR=29,3). In this situation, it is recommended that moms of young children monitor their toddlers' food intake by offering a variety of foods in portions that meet their needs.